2006
DOI: 10.1111/j.1365-2966.2006.10637.x
|View full text |Cite
|
Sign up to set email alerts
|

Shapley Optical Survey - II. The effect of environment on the colour-magnitude relation and galaxy colours★

Abstract: We present an analysis of the effects of environment on the photometric properties of galaxies in the core of the Shapley supercluster at z= 0.05, one of the most massive structures in the local universe. The Shapley Optical Survey (SOS) comprises archive Wide Field Imager (WFI) optical imaging of a 2.0 deg2 region containing the rich clusters A3556, A3558 and A3562 which demonstrate a highly complex dynamical situation including ongoing cluster mergers. The B−R/R colour–magnitude relation has an intrinsic dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 59 publications
5
58
0
Order By: Relevance
“…Balogh et al 1999;Lewis et al 2002;Gómez et al 2003;Finn et al 2005). It is also consistent with the result that the relative fraction of blue galaxies peaks between 1 and 2 R Vir in the nearby Shapley and Pisces-Cetus superclusters (Haines et al 2006;Porter & Raychaudhury 2006).…”
Section: Discussionsupporting
confidence: 78%
“…Balogh et al 1999;Lewis et al 2002;Gómez et al 2003;Finn et al 2005). It is also consistent with the result that the relative fraction of blue galaxies peaks between 1 and 2 R Vir in the nearby Shapley and Pisces-Cetus superclusters (Haines et al 2006;Porter & Raychaudhury 2006).…”
Section: Discussionsupporting
confidence: 78%
“…Our study shows the importance of the role of superclusters as high density environment which affects the properties of galaxies and galaxy systems in them (Plionis 2004;Wolf et al 2005;Haines et al 2006;Einasto et al 2007c;Porter et al 2008;Tempel et al 2009;Fleenor & Johnston-Hollitt 2010;Tempel et al 2011;Einasto et al 2011e). Earlier studies of galaxy superclusters revealed that while according to their overall properties superclusters can be described with a small number of parametres (Einasto et al 2011c), the analysis of the morphology and galaxy and group content of the richest superclusters from the 2dF Galaxy Redshift Survey and from the Sloan Great Wall with SDSS data ) demonstrate a large variety of supercluster morphologies and differences in the distribution of galaxies from various populations, and groups of galaxies in superclusters.…”
Section: Discussionmentioning
confidence: 99%
“…This makes them ideal laboratories to study processes that affect the evolution of galaxies, groups, and clusters of galaxies. A number of studies have already shown that the supercluster environment affects the properties of galaxies, groups, and clusters located there (Einasto et al 2003b;Plionis 2004;Wolf et al 2005;Haines et al 2006;Einasto et al 2007c;Porter et al 2008;Tempel et al 2009;Fleenor & Johnston-Hollitt 2010;Tempel et al 2011;Einasto et al 2011). Other evidence about the influence of the largescale environment of galaxies on their properties comes from the study of the properties of galaxies in void walls (Ceccarelli et al 2008) and from the study of the large-scale environment of quasars (Lietzen et al 2009).…”
Section: Introductionmentioning
confidence: 99%